Comparison of an X-ray-selected sample of massive lensing clusters with the MareNostrum Universe [Lambda] CDM simulation - Meneghetti, Massimo; Fedeli, Cosimo; Zitrin, Adi; Bartelmann, Matthias (Arxiv, 2011)
A long-standing problem of strong lensing by galaxy clusters regards the observed high rate of giant gravitational arcs as compared to the predictions in the framework of the "standard" cosmological model. Recently, few other inconsistencies between theoretical expectations and observations have been claimed which regard the large size of the Einstein rings and the high concentrations of few clusters with strong lensing features. All of these problems consistently indicate that observed galaxy clusters may be gravitational lenses stronger than expected. We use clusters extracted from the MareNostrum Universe to build up mock catalogs of galaxy clusters selected through their X-ray flux. We use these objects to estimate the probability distributions of lensing cross sections, Einstein rings, and concentrations for the sample of 12 MACS clusters at $z>0.5$ presented in Ebeling et al. (2007) and discussed in Zitrin et al. (2010). We find that simulated clusters produce $\sim 50%$ less arcs than observed clusters do. The medians of the distributions of the Einstein ring sizes differ by $\sim 25%$ between simulations and observations. We estimate that, due to cluster triaxiality and orientation biases affecting the lenses with the largest cross sections, the concentrations of the individual MACS clusters inferred from the lensing analysis should be up to a factor of $\sim 2$ larger than expected from the $Λ$CDM model. The arc statistics, the Einstein ring, and the concentration problems in strong lensing clusters are mitigated but not solved on the basis of our analysis. Nevertheless, due to the lack of redshifts for most of the multiple image systems used for modeling the MACS clusters, the results of this work will need to be verified with additional data. The upcoming CLASH program will provide an ideal sample for extending our comparison (abridged).